Analisis Pengaruh Size, Profitabilitas, Likuiditas Dan Leverage Terhadap Peringkat Obligasi (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia periode 2013-2015) - Ariana, Devy, Drs. Agus Endro Suwarno, M.Si (2017)
This research aims to provide empirical evidence about the influence of size, profitability, liquidity and leverage against bond rating on the banking company. The data used are secondary data are derived from the financial statements, banking company listed on the Indonesia stock exchange and bond ratings data from PT PEFINDO period 2013-2015 respectively. The population in this research is the banking company listed on the Indonesia stock exchange and bond ratings data from PT PEFINDO period 2013-2015 respectively. Method of determination of the sample used i.e. purposive sampling, the number of samples based on predetermined criteria is 69 sample banking company. Methods of analysis are either ordinal logistic regression (PLUM). Based on the results of the analysis of partially indicate that size as measured using Ln Total assets rank effect on bonds. While profitability measured by ROA, liquidity is measured by the current ratio and leverage as measured by the DER does not affect the bond ratings. Key words: size, profitability, liquidity, leverage, bond ratings